Waterleaf, a Potential Leafy Vegetable for Florida - Christianah Oladoye; Guodong Liu (EDIS)
Waterleaf is a vegetable crop whose edible leaves are soft, succulent, and highly nutritious. It is available in some local grocery stores in Florida but is new to most people in Florida and its environs. Waterleaf production is economically attractive due to low cost for seeds, pesticides, and herbicides for producing the crop. Like other leafy vegetables, waterleaf can be grown in home gardens as well. This new 6-page article will give an overview of this emerging vegetable in Florida. The intended audience is county Extension faculty, students, growers, and consumers. Written by Christianah T. Oladoye and Guodong Liu and published by the UF/IFAS Horticultural Sciences Department.